2020
DOI: 10.3892/mco.2020.1991
|View full text |Cite
|
Sign up to set email alerts
|

Network‑based identification of signature genes KLF6 and SPOCK1 associated with oral submucous fibrosis

Abstract: The molecular mechanism of oral submucous fibrosis (OSF) is yet to be fully elucidated. The identification of reliable signature genes to screen patients with a high risk of OSF and to provide oral cancer surveillance is therefore required. The present study produced a filtering criterion based on network characteristics and principal component analysis, and identified the genes that were involved in OSF prognosis. Two gene expression datasets were analyzed using meta-analysis, the results of which revealed 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Starkel et al reported that oxidative stress, KLF6 and TGF-β1 upregulation discriminate non-alcoholic steatohepatitis advancing to fibrosis from uncomplicated steatosis in rats 46 . www.nature.com/scientificreports/ Furthermore, accumulating evidence demonstrates that KLF6 is involved in the occurrence of oral submucous fibrosis 47 . BCL2L11, also known as BIM, is a pro-apoptotic member of the B cell CLL/lymphoma 2 protein family and is an essential modulator of apoptosis 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Starkel et al reported that oxidative stress, KLF6 and TGF-β1 upregulation discriminate non-alcoholic steatohepatitis advancing to fibrosis from uncomplicated steatosis in rats 46 . www.nature.com/scientificreports/ Furthermore, accumulating evidence demonstrates that KLF6 is involved in the occurrence of oral submucous fibrosis 47 . BCL2L11, also known as BIM, is a pro-apoptotic member of the B cell CLL/lymphoma 2 protein family and is an essential modulator of apoptosis 48 .…”
Section: Resultsmentioning
confidence: 99%
“…The 18 infected samples were studied at different time points of Day1, Day2, Day3, Day5, Day14, and Day28, respectively. The relative expression levels of a gene symbol mapping to multiple probeset IDs were averaged and the probeset IDs with no corresponding gene symbol were eliminated ( Ahmad et al, 2019 , Shriwash et al, 2019 , Singh et al, 2020 ). A three-stage screening protocol was employed to screen the significant differentially expressed genes (DEGs) between two infection status groups, i.e., uninfected vs infected.…”
Section: Methodsmentioning
confidence: 99%
“…Probe IDs were mapped to their corresponding HUGO Gene Nomenclature Committee (HGNC) gene symbol(s) using the GPL570 annotation file and hgu133plus2.db package available in R v4.0.2. Expression values of duplicate gene symbols mapping to multiple probe IDs were averaged across the samples [20,21] in both the datasets followed by p-value computation of all unique genes using two-sample paired t-test function. Common genes from both the datasets were identified using the intersect function.…”
Section: Nsclc-associated Microarray Data Extractionmentioning
confidence: 99%